PEMANFAATAN APLIKASI E-COMMERCE BERBASIS WEB MENGGUNAKAN FRAMEWORK CODEIGNITER (STUDI KASUS : DISTRO PAK EKO) - yustina meisella kristania (Universitas Bina Sarana Informatika, 2019)
Abstract - The progress of internet technology for now is very helpful in almost all fields of life, including in the business sector of commerce. E-commerce is one of the technologies that support the development of today's trading world. Online sales can make it easier for small to medium-sized businesses because of the lack of capital for financing rental premises, determining strategic marketing points, to the amount of electricity financing. This website application is an online sales system using internet technology, to facilitate prospective buyers in conducting transactions through this media. The web-based e-commerce application on Eko Distro is made using the PHP programming language with the CodeIgniter framework and MySQL database. Analysis of problems in the development of e-commerce applications uses analysis and PIECES requirements. It is expected that with the existence of an additional service door at Distro, Pak Eko will be able to facilitate the long-distance transaction process besides having to visit the distro for a long time.Keywords: internet, e-commerce, website, framework codeigniterAbstrak - Kemajuan teknologi internet untuk saat ini sangat membantu hampir diseluruh bidang kehidupan, termasuk pada bidang usaha perdagangan. E-commerce merupakan salah satu teknologi yang mendukung perkembangan dunia perdagangan saat ini. Penjualan online dapat mempermudah badan usaha kecil hingga menengah karena sedikitnya modal pembiayaan sewa tempat, penentuan titik strategis pemasaran, sampai dengan besarnya pembiayaan listrik. Aplikasi website ini adalah sebuah sistem penjualan online menggunakan teknologi internet, untuk mempermudah calon pembeli dalam melakukan transaksi melalui media ini. Aplikasi e-commerce berbasis web pada Distro Pak Eko ini dibuat menggunakan bahasa pemrograman PHP dengan framework CodeIgniter dan basis data MySQL. Analisis masalah dalam pengembangan aplikasi e-commerce ini menggunakan analisis dan kebutuhan PIECES. Diharapkan dengan adanya satu pintu layanan tambahan pada Distro Pak Eko ini akan mampu memudahkan dalam proses transaksi jarak jauh selain harus mengunjungi distro dengan waktu yang lama.Kata kunci : internet, e-commerce, website, framework codeigniter